Isolation and selection of Glyphosate herbicide tolerant fungi (Research, Society and Development, 2022)
The objective of this work was to isolate fungi from an ecological reserve in the Brazilian Midwest and to select species tolerant to glyphosate, a herbicide widely used in agriculture. The purified isolates were subjected to qualitative tests to assess the oxidizing capacity of gallic acid and RBBR dye discoloration. Then, the selected fungi were identified through molecular biology techniques and used in herbicide tolerance tests. Fungal growth rates (FG) and fungal growth inhibition (FGI) in the absence and presence of different concentrations of glyphosate (10 mg mL-1, 30 mg mL-1 and 50 mg mL-1) were evaluated. For statistical analysis, a double factorial scheme (fungus and concentration) was used, followed by the Tukey test (p ≤ 0.05). A total of 44 fungi were isolated in the field, having a purification efficiency of 50%. Of these, 60% showed positive results in the gallic acid test and 45.5% were positive for RBBR discoloration. The seven fungi selected from the qualitative tests were tolerant to the herbicide glyphosate, with Phanerochaete australis SA18 standing out with higher FG, lower FGI and mycelial growth significantly higher compared to other fungi in all tests. Thus, the use of P. australis SA18 is recommended for further studies on the production of ligninolytic enzymes, degradation and production of glyphosate metabolites and tests on bioremediation of contaminated agricultural soils.